Contraceptive Use Before First Birth in North-East India: Trends and Socio-Demographic Inequalities Based on NFHS Data - Heisnam Ruhi Singh; Kshetrimayum Anand Singh (National Journal of Community Medicine)
Background: Taking part in human reproduction immediately after marriage will not be a good choice for those young couples from the point of view of population growth as well as the health of the mother and the newborn. As such, postponement of the first birth will benefit both the newborn's and the mother's health. The use of contraceptives before the first birth is a reasonable choice for delaying it. The objective of this paper is to analyse the trends in contraceptive use before first birth and to explore and identify potential socio-demographic covariates that significantly influence this trend in North-East India.